1998
DOI: 10.1074/jbc.273.42.27300
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor-BB and Thrombin Generate Positive and Negative Signals for Human Hepatic Stellate Cell Proliferation

Abstract: Proliferation of myofibroblastic hepatic stellate cells (HSC) in response to growth factors is essential for the development of liver fibrosis. We have reported that prostaglandins (PG) and cyclic AMP (cAMP) inhibit growth of human HSC. This PG/cAMP pathway transduces the endothelin (ET) B-mediated antiproliferative effect of endothelin-1 (ET-1) and up-regulates ETB receptors. Here, we show that platelet-derived growth factor (PDGF)-BB and thrombin, although mitogenic, generate growth inhibitory PGE 2 in myofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 40 publications
11
83
0
1
Order By: Relevance
“…As shown in Figure 8A, pretreatment with ibuprofen exerted a dose-related abrogation of the inhibitory effect of NO donors on PDGF-induced DNA synthesis. In addition, pretreatment with ibuprofen significantly enhanced the mitogenic effect of PDGF, similar to the data of Mallat et al 51 Accordingly, the observed inhibition of PDGF-induced ERK activity exerted by NTG and SNAP was completely abolished when cells were preincubated with ibuprofen ( Figure 8B). Finally, to characterize the involvement of the adenylate cyclase/ cAMP pathway, we examined intracellular cAMP synthesis in response to NO donors in the absence and presence of ibuprofen.…”
Section: Pge 2 Synthesis Blockade Abrogates the Inhibitory Effect Of supporting
confidence: 89%
See 2 more Smart Citations
“…As shown in Figure 8A, pretreatment with ibuprofen exerted a dose-related abrogation of the inhibitory effect of NO donors on PDGF-induced DNA synthesis. In addition, pretreatment with ibuprofen significantly enhanced the mitogenic effect of PDGF, similar to the data of Mallat et al 51 Accordingly, the observed inhibition of PDGF-induced ERK activity exerted by NTG and SNAP was completely abolished when cells were preincubated with ibuprofen ( Figure 8B). Finally, to characterize the involvement of the adenylate cyclase/ cAMP pathway, we examined intracellular cAMP synthesis in response to NO donors in the absence and presence of ibuprofen.…”
Section: Pge 2 Synthesis Blockade Abrogates the Inhibitory Effect Of supporting
confidence: 89%
“…Along these lines, established experimental evidence obtained in activated human HSCs has clearly shown that activation of this signaling pathway is associated with effects on PDGF action and signaling similar to those observed in the presence of NO donors. [51][52][53] In agreement with this alternative working hypothesis, PGE 2 synthesis blockade obtained by using the COX inhibitor ibuprofen results in a decrease in NO donor-induced cAMP synthesis and in abrogation of the inhibitory effect of NO donors on both PDGF action and intracellular signaling.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Indeed, we found that the antiproliferative effects of ET-1 and TNF-␣ involve COX-2 (6). We also showed that the mitogenic effects of PDGF-BB and thrombin result from a balance between a promitogenic and a COX-2-dependent growth inhibitory pathway (5). Therefore, the present data further support a central role of COX-2 in hMF growth inhibition.…”
Section: Discussionsupporting
confidence: 69%
“…IL-1β-induced COX-2 expression was enhanced by IGF-I treatment in rat renal mesangial cells (23). However, other recent studies showed that IGF-I failed to induce COX-2 expression in HT-29 colon cancer cells, hepatic stellate cells, and human vein vascular endothelial cells (13,24,25), and IGF-I treatment even decreased COX-2 expression in osteoblasts (26). Thus, the effects of IGF-I on COX-2 expression appear to be cell-type specific, which may reflect its ability to promote organ-specific tumorigenesis (2-4).…”
Section: Discussionmentioning
confidence: 99%